The Second Amendment of Electronic Information and Transaction Law: Pros and Cons of Human Rights Perspectives - Nisa, Ardina Khoirun (JURNAL ILMIAH GEMA PERENCANA, 2025)
The government demands the active participation of the public in criticizing the government. However, this statement has sparked controversy among various groups. The purpose of this writing is to understand the response of students regarding the government's demand to be criticized while being threatened by the Information and Electronic Transactions Law, an Indonesian term using ITE Law. It also discusses the legal safeguards needed to protect individuals from criminal sanctions when criticizing the government. This research uses normative research methods, which involve analysing issues based on legislation and legal literature. The existence of the ITE Law has caused concerns among the public regarding giving criticism and feedback to the government through social media platforms. One of the main concerns lies in the ambiguous interpretation of certain articles, particularly Articles 27A and 27B concerning defamation of character. The lack of clear boundaries regarding the elements of defamation of character poses several challenges in the implementation of these articles, including restrictions on freedom of expression guaranteed by the constitution and human rights. In other words, the ambiguity of these articles hinders the achievement of legal objectives such as certainty, usefulness, and justice. The implementation of the latest revision of the ITE Law should be carried out fairly and transparently, ensuring legal certainty in handling cases involving the ITE Law, to alleviate excessive concerns.